2022
DOI: 10.1155/2022/1382940
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Determinants of Anemia among Under-Five Children in Africa: Systematic Review and Meta-Analysis

Abstract: Introduction. Globally, anemia among under-five children is a serious public health problem. Even if there are pocket studies here and there, there is limited evidence on the pooled prevalence of anemia among under-five children in Africa. Therefore, the aim of this study was to determine the pooled prevalence and determinants of anemia. Methods and Analysis. This systematic review and meta-analysis was done following the PRISMA guidelines. A comprehensive search was made in PubMed/MEDLINE, Cochrane Library, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 56 publications
1
16
1
1
Order By: Relevance
“…[ 51 ] The reason for this might be the relative homogeneity of the study population. In particular, the mother’s education level was not found to be a determinant of child anemia in contrast to existing evidence [ 14 , 15 , 16 , 21 , 52 , 53 ]. However, this is in line with findings from our main study on the determinants of anemia among Syrian mothers, previous studies conducted in Lebanon among Lebanese children aged 11 to 75 months of age and Lebanese women of reproductive age whereby the authors could not find any associations between socio-economic variables and the hematological status of the respective study participants [ 18 , 52 , 54 , 55 ].…”
Section: Discussioncontrasting
confidence: 92%
“…[ 51 ] The reason for this might be the relative homogeneity of the study population. In particular, the mother’s education level was not found to be a determinant of child anemia in contrast to existing evidence [ 14 , 15 , 16 , 21 , 52 , 53 ]. However, this is in line with findings from our main study on the determinants of anemia among Syrian mothers, previous studies conducted in Lebanon among Lebanese children aged 11 to 75 months of age and Lebanese women of reproductive age whereby the authors could not find any associations between socio-economic variables and the hematological status of the respective study participants [ 18 , 52 , 54 , 55 ].…”
Section: Discussioncontrasting
confidence: 92%
“…The risk of anemia was found to be higher in children below two years, male children, children born to adolescent mothers, children born to non-Christian homes, children whose mothers were not covered with health insurance, leaving in either upper west or central region and children born to families of poorer households. Our ndings' revealed anemia was prevalent among 54% of children under ve, an estimate lower than 76.6% in Sub-Sahara Africa [33] but reasonably higher in other sub-Sahara Africa countries [13,34] and global estimates of 40.0% in 2019 [16,35]. Although the World Health Organization considers anemia prevalence greater than 40% as a severe public health problem, ndings from this study and another study showed that Ghana's anemia prevalence in children under-ve years has reduced from 78% in 2008 to 66% in 2014 and further to 54% in 2019 which implies anemia intervention control programs implemented are gradually in uencing the population [36].…”
Section: Factors Associated With Anemia In Children Under-ve From The...mentioning
confidence: 47%
“…In addition, increase in household size was found to be associated with increased risk of anemia among children. This is supported by ndings from elsewhere in Ethiopia [42] and a systematic review in Africa [13]. Reducing household crowding, improving toilet and water facilities helped in reducing the risk of anemia in children underve years [34].…”
Section: Factors Associated With Anemia In Children Under-ve From The...mentioning
confidence: 87%
See 1 more Smart Citation
“…Since timely detection and treatment of anemia improves population health outcomes, physical capacity building, and well-being, resulting in increased economic growth. 18 The major contribution to this study is the use and combination of three (3) different dataset, that is, the conjunctiva of the eye, palpable palm and color of the fingernail images for the detection of iron deficiency anemia. In addition, this study compared the performance of five (5) machine learning models while most studies applied a single model or two to detect anemia.…”
Section: Introductionmentioning
confidence: 99%